Analisis Kontribusi dan Peran Basis Sektor Pertanian, Kehutanan, dan Perikanan terhadap PDRB Kabupaten Kampar Tahun 2020–2024 - M. Zaky Syaputra; Farhan Zharfa Razani; Taryono (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
The study evaluates the contribution, growth rate, and role of the agriculture, forestry, and fisheries sector toward the Gross Regional Domestic Product (GRDP) of Kampar Regency (2020–2024). Secondary BPS data was analyzed using sectoral contribution analysis, growth rate, and the Location Quotient (LQ). The results indicate the sector contributes an average of 30–35 percent to GRDP and consistently functions as a basic (leading) sector (LQ > 1). Critically, the growth rate experienced a significant slowdown to 2.45% in 2024, suggesting vulnerability to global commodity price volatility and the potential for a resource trap. This finding necessitates policy interventions, including innovation, technological modernization, and downstream industrialization to mitigate over-reliance on raw natural resources. Policy-wise, the study supports the Kampar Regency Regional Development Plan (RPD) 2023–2026, which emphasizes strengthening commodity value-added and sustainable development.